SUPPORT SYSTEM AND QUALITY OF LIFE OF POST-COVID-19 PATIENTS IN ENDE REGENCY, EAST NUSA TENGGARA PROVINCE - Syaputra Artama; Irfan Irfan; Aris Wawomeo (Proceeding B-ICON, 2022)
The COVID-19 pandemic has caused a change in habits for patients after COVID-19 in Indonesia. Social stigma and negative perceptions of the COVID-19 disease can also have an impact on post-COVID-19 patients. Both informal and formal support systems are critical to the successful care and recovery of patients post COVID-19. This study aims to determine the support system on the quality of life in patients with post-COVID-19 in Ende Regency. The type of research used is analytical. The results of the study found that there was a significant relationship between the support system and the quality of life of patients after COVID-19 (p = 0.001) with a correlation value of r = 0.567. The conclusion that the support system with the quality of life of patients post-COVID-19 has a positive correlation. The better the support system provided and received by patients after COVID-19, the better their quality of life will be.observational using a cross sectional study design. The sampling method uses cluster random sampling. The sample used the proportional allocation technique with a sample of 110 respondents. The results of the study found that there was a significant relationship between the support system and the quality of life of patients after COVID-19 (p = 0.001) with a correlation value of r = 0.567. The conclusion that the support system with the quality of life of patients post-COVID-19 has a positive correlation. The better the support system provided and received by patients after COVID-19, the better their quality of life will be